Hansel and Gretel - Barrie; J.M. (London Dreamland Publications, 2011)
The tale follows siblings Hansel and Gretel, who are abandoned in the forest by their stepmother. They stumble upon a gingerbread house owned by a wicked witch. The witch captures them with the intention of eating them, but the clever children use their wits to outsmart her. They manage to escape and find their way back home. The story highlights themes of bravery, resourcefulness, and the bond between siblings.